State injustice: trapping black women as "sex offenders" for prostitution in "the Big Easy" - Sheets, Crystal Faye, author; Bubar, Roe, advisor; Cespedes, Karina, committee member; Valdez, Norberto, committee member; Daum, Courtenay, committee member (Colorado State University. Libraries, 2012)
This qualitative case study explores the use of a sodomy statute, Crime Against Nature, to criminalize prostitution and its impacts on impoverished Black women located on the streets of New Orleans. Data from in-depth interviews with six participants including a Public Defender, a Prosecutor, a Judge, a Community Worker, and two sex workers, were studied through a critical feminist analytic framework to decipher prevalent themes regarding the state's implementation of this charge. Major findings include: intersecting race/class/gender oppressions socially track or position Black women in the street sex economy where they are targeted by the state, the regulation of prostitution is performed in ways which permit a sex economy in the French Quarter to cater to tourists while it criminalizes prostitution in poor areas outside of the French Quarter, drug addiction is used as justification by the state to criminalize Black women on the street using this charge, and the ways in which recipients of this charge are further burdened and trapped by the state, which labels them felons and sex offenders rather than offering assistance and protection.